2015
DOI: 10.1021/acs.nanolett.5b02404
|View full text |Cite
|
Sign up to set email alerts
|

Fast Anion-Exchange in Highly Luminescent Nanocrystals of Cesium Lead Halide Perovskites (CsPbX3, X = Cl, Br, I)

Abstract: Postsynthetic chemical transformations of colloidal nanocrystals, such as ion-exchange reactions, provide an avenue to compositional fine-tuning or to otherwise inaccessible materials and morphologies. While cation-exchange is facile and commonplace, anion-exchange reactions have not received substantial deployment. Here we report fast, low-temperature, deliberately partial, or complete anion-exchange in highly luminescent semiconductor nanocrystals of cesium lead halide perovskites (CsPbX3, X = Cl, Br, I). By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

90
2,129
6
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 2,107 publications
(2,236 citation statements)
references
References 53 publications
90
2,129
6
11
Order By: Relevance
“…The size dependence at low temperature triggered works by Nedelcu et al and Akkerman et al in which the halide ratios were adjusted; they found a fast anion and inter-nanocrystal anion exchange in cesium lead halide perovskite CsPbX 3 (X = Cl, Br, I) at room temperature, which led to continuous formation of homogeneous CsPb(Cl/Br) 3 or CsPb(Br/I) 3 compositions. [64] With proper adjustment of the halide ratios, the tunable photoluminescence was observed over the visible regime 410-700 nm without sacrificing high quantum yields from 20-80%. Inspired by these works, Swarnkar et al further demonstrated CsPbBr 3 colloidal NPs based on the methods discussed above.…”
Section: D Perovskite: Quantum Dots (Qds)mentioning
confidence: 99%
See 1 more Smart Citation
“…The size dependence at low temperature triggered works by Nedelcu et al and Akkerman et al in which the halide ratios were adjusted; they found a fast anion and inter-nanocrystal anion exchange in cesium lead halide perovskite CsPbX 3 (X = Cl, Br, I) at room temperature, which led to continuous formation of homogeneous CsPb(Cl/Br) 3 or CsPb(Br/I) 3 compositions. [64] With proper adjustment of the halide ratios, the tunable photoluminescence was observed over the visible regime 410-700 nm without sacrificing high quantum yields from 20-80%. Inspired by these works, Swarnkar et al further demonstrated CsPbBr 3 colloidal NPs based on the methods discussed above.…”
Section: D Perovskite: Quantum Dots (Qds)mentioning
confidence: 99%
“…[142] Halide exchange has been adopted to create mixed halide perovskites with tunable PL wavelengths that cover the entire visible spectrum. [64,89,143] The rapid ion exchange reactions allude to facile ion migration in PSCs, but the identity and circumstances for ion conduction have remained uncertain because of the reversible processes and the lack of spatial distribution of the elemental composition in operation. Fortunately, a series of theoretical and experimental investigations have unequivocally established that halide, ammonium, and perhaps even proton migration (transiently) deteriorate the perovskite optoelectronic properties.…”
Section: Ion Migrationmentioning
confidence: 99%
“…4A, Inset), indicating effective waveguiding and coherent emission from the nanowire. Halide alloying may be pursued in the future to achieve broad wavelength tunability as observed in CsPbX 3 quantum dots and CH 3 NH 3 PbX 3 materials (20,41). In addition to nanowires, well-faceted CsPbBr 3 nanoplates were found to lase at ∼38 μJ cm −2 with the power-dependent emission spectra shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Dialectically, the fast anion exchange reaction between different halide NCs has caused issues in broadening emission spectra and chromaticity drifts while using this great concept for color tuning 4. Recently, some examples have been demonstrated to resolve this problem.…”
Section: Introductionmentioning
confidence: 99%